Superimposed Nephrotic Syndrome in Diabetic Patients: 15 Cases of Mismatched Clinicopathological Correlation - El-Reshaid, Kamel; Al-Bader, Shaikha (International Journal of Innovative Research in Medical Science, 2020)
The spectrum of renal disease in patients with diabetes encompasses both diabetic kidney disease (including albuminuric and non-albuminuric phenotypes) and non-diabetic kidney disease (NDKD). Acute nephrotic syndrome (NS) with short duration of diabetes indicates NDKD. Moreover, such presentation is atypical in patients with IgA nephropathy and pre-eclampsia and hence warrants kidney biopsy to rule out treatable glomerulopathy. In this case series; we present our experience with 15 patients with atypical NS and outline their management.